Discoloration and Degradation of Bamboo under Ultraviolet Radiation - Haixia Yu; Shengliang He; Wenfu Zhang; Mengyao Zhan; Xiaowei Zhuang; Jin Wang; Wenji Yu (International Journal of Polymer Science)
Light is one of the most adverse factors for bamboo deterioration and causes surface degradation and discoloration. The study was carried out to initiate efficient and effective photodiscoloration to modify and enrich bamboo colors that may be applied to bamboo dyeing. Different types of bamboo samples commonly used in the industry were studied experimentally under two types of ultraviolet (UV) light. Effects of light sources, radiation time, and distances on discoloration and discoloration mechanism were systematically studied. For both UV 313 and high-pressure mercury light, the bamboo surface turned red-yellow, and color parameters including ΔE, Δa, Δb, and C rapidly increased first and then stabilized for long time, while ΔL showed a similar trend, except for the final decrease. Compared with UV 313, high-pressure mercury lamp light was highly efficient and took less time to induce discoloration. Heat treatments darkened the bamboo color and slowed down photodiscoloration, and the higher temperature led to more photostability. The color change of bamboo scrimber under UV radiation was less and slower than that of untreated bamboo due to high density and heat treatment, and the dark carbonized scrimber changed less than that of the light carbonized scrimber. Relatively high contents of isovanillin, syringaldehyde, β-hydroxypropiovanillone, p-hydroxybenzaldehyde, and syringic acid were identified by GC-MS, and syringaldehyde, 2,6-dimethylbenzoquinone, and 3-hydroxy-4-methoxybenzoic acid were identified by HPLC-MS from a bamboo discoloration layer after high-pressure mercury lamp radiation. These products all contained a conjugated double bond and were conjectured to be degraded from lignin or aromatic extracts. Particularly, 2,6-dimethylbenzoquinone which contained a cyclohexenedione structure without benzene rings, was more chemically stable than other conjugated double bonds with benzene rings, and was supposed to be the final product (chromogenic group) during bamboo photodegradation. Untreated or light-colored bamboo under high-energy UV light initiated highly efficient and effective photodiscoloration, and UV light is recommended for being applied to industrial bamboo dyeing. Compared with traditional chemical dyeing, the photoinduced dyeing method has no chemical addition and is easy to operate and environmental-friendly.